The Relationship Between the Key Policy Rate and Macroeconomic Variables: A Simple Cross-Check for Norway - Tom Bernhardsen (Norges Bank, 2008)
In this paper we discuss simple relationships between the key policy rate and macroeconomic variables in Norway. Such models may be useful tools in monetary policy analysis as they provide a cross-check for the interest rate. This study is an update of Bernhardsen and Bardsen (2004), who estimate similar models for the period 1999-2004. An estimated relationship between the policy rate and macroeconomic variables can be interpreted as reflecting the central bank's average reaction pattern in monetary policy given the development of macroeconomic variables in the past. However, an estimated equation of this kind can not be interpreted as "the reaction function of the central bank". The actual interest rate setting is based on a vast amount of information about economic developments, macroeconomic equilibrium models and - not least - experience and judgment. No central bank follows simple cross-checks when setting the interest rate. Still, simple cross-checks may give guidance in the process of interest rate setting and if the actual interest rate deviates considerably from simple cross-checks, one should be able to explain why. Moreover, we should recall that econometrics is not an exact science. In the estimation process emphasis is put on economic theory, experience about the Norwegian economy, judgement and econometric evidence.
hdl:11250/2507965
Keywords: 330